Effect of characteristic parameters of pitting on strength and stress concentration factor of cable steel wire. (20th April 2020) - Li, Rou; Miao, Changqing; Yu, Jie
Highlights: The effect of pits on the stress concentration factor of steel wires is investigated. Parametric analyses were performed on steel wire with different pits parameters. The formula of stress concentration factor of steel wire with pits was established. Abstract: In order to investigate the influence of characteristic parameters of pits on the strength and stress concentration factor of cable steel wire, 198 cable steel wires with pits were manually prepared. The variation law of stress distribution of steel wire was analyzed, and its relationships with strength and stress concentration factor were studied through tensile test and finite element analysis. On this basis, the calculation model of yield strength and stress concentration factor of steel wire with pits was established. The influences of secondary pits on stress distribution and stress concentration factor of steel wire were also analyzed. The results showed that the strength of steel wire decreased gradually and the stress concentration factor increased with the increase of pit depth and the decrease of pit width. The change of pit clearance on the same side had no obvious effect on the strength and stress concentration factor of steel wire, but it had significant effect when located on the opposite side. The strength and stress concentration factor of steel wire with adjacent pits usually depended on the depth of the larger pits. The pits with depth to width ratio of 1 to 2 had the most significant effect on the stress concentration factor. Moreover, secondary pit would change the stress distribution, and the position of maximum stress changed from near the mouth to the bottom of the pit. The stress concentration factor of secondary pit was obviously higher than that of steel wire with only the primary pit.